A New Class of Carbon Nanostructures for High‐Performance Electro‐Magnetic and ‐Chemical Barriers (Adv. Sci. 22/2021). Issue 22 (17th November 2021) - Park, Jae Hui; Oh, Yun Ji; Park, Dong Yoon; Lee, Joonsik; Park, Jae Seo; Park, Chong Rae; Kim, Jae Ho; Kim, Taehoon; Yang, Seung Jae
Abstract : Design of New Carbon Nanostructures In article number 2102718, Jae Ho Kim, Taehoon Kim, Seung Jae Yang, and co‐workers demonstrate a new carbon nanostructure consisting of interconnected N‐doped graphitic nanocubes embedding nickel nanoparticles. Distinctive structural features impart crucial functions desirable for the electromagnetic and electrochemical barriers. This study gives new insights into structural design of the carbon nanostructure for high‐performance electromagnetic and electrochemical barriers.